INTEGRASI PBL, STAD, DAN SNOWBALL THROWING UNTUK OPTIMALISASI PEMBELAJARAN MATEMATIKA BERBASIS BERPIKIR KRITIS - Indriyanti; Darmiyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research was motivated by the low learning activity, critical thinking skills, and mathematics achievement of fifth-grade students at SDN Pasar Lama 3 Banjarmasin. These issues emerged due to the lack of student engagement in the learning process, the use of monotonous teaching strategies, and the absence of instructional models that support the development of higher-order thinking skills. As a result, students became passive, struggled to analyze problems, and failed to meet the expected learning standards. To address these problems, a combination of Problem Based Learning (PBL), Student Teams Achievement Division (STAD), and Snowball Throwing models was implemented. The objective of this study was to describe teacher and student activities, as well as to analyze students' critical thinking skills and learning outcomes following the application of the combined models. The research employed a Classroom Action Research (CAR) method using both qualitative and quantitative approaches. Data were collected through observation and written tests, and analyzed using percentages and learning mastery criteria. The findings revealed a significant improvement in both teacher and student activities, enhancement of students' critical thinking skills, and better mathematics learning outcomes, meeting both individual and classical mastery criteria. Therefore, the integration of these three instructional models proved effective in fostering active, reflective, and meaningful learning experiences. These results are recommended as a reference for selecting appropriate learning models at the elementary school level.